High Prevalence of Vitamin D Deficiency and Adverse Pregnancy Outcomes in Yazd, a Central Province of Iran - Pirdehghan, Azar (J Reprod Infertil, 2016)
BACKGROUND: There is a growing concern about the high prevalence of vitamin D deficiency and its relationship with variety of diseases worldwide. The objective of this study was to determine the prevalence of vitamin D deficiency and its relationship with pregnancy adverse effects in Yazd. METHODS: This was a cross sectional study conducted among 200 nulliparous women from October 2013 to April 2014. Data containing socio-demographic and personal details, vitamin D level, pregnancy complications and growth situation of newborns were collected and analyzed using Mann-Whitney, Kruskal-Wallis and Pearson's correlation coefficient by SPSS. p<0.05 was considered statistically significant. RESULTS: The mean serum 1, 25 (OH)(2)D(3) concentration was 20.3±10.8 μg/l. Totally, 78% of the women had less than sufficient levels. Mean of vitamin D was significantly higher in natural or elective cesarean in comparison with abortion and emergency cesarean (p=0.040). Risk of abortion was 3.1(1.39–6.8) and higher in severely deficient group in comparison to women with vitamin D deficiency (p=0.017) and mean of vitamin D group was significantly lower in women who had oligohydramnios or polyhydramnios complication (p=0.045). CONCLUSION: The study findings revealed that vitamin D deficiency is prevalent in pregnant women and it is significantly associated with elevated risk for abortion, and oligohydramnios or polyhydramnios. Probably, a targeted screening strategy can be suggested to detect and treat women at high risk of vitamin D deficiency in early pregnancy as a simple way to reduce the risk of these adverse pregnancy outcomes in Yazd.